(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Local governance plays a decisive role in shaping municipal strategies for sustainability, environmental protection, and climate adaptation. Municipal authorities, being the closest layer of government to communities, are uniquely positioned to implement targeted policies, manage resources efficiently, and address localized climate risks risks. This article examines how governance quality, stakeholder engagement, and institutional capacity influence environmental outcomes. It highlights successful policy models, identifies barriers such as political fragmentation and funding gaps, and assesses the integration of climate adaptation measures into urban planning . By exploring case case-based evidence, the analysis demonstrates that effective local governance is not just an administrative necessity necessity—it is a critical driver for building resilient, low low-carbon, and sustainable cities in the face of accelerating climate challenges.